Reliability-Based Optimal Bidding Strategy of a Technical Virtual Power Plant - Pourghaderi, Niloofar; Fotuhi-Firuzabad, Mahmud; Kabirifar, Milad; Moeini-Aghtaie, Moein; Lehtonen, Matti; Wang, Fei (IEEE systems journal, 2022)
Technical virtual power plant (TVPP) aggregates distributed energy resources in order to trade in wholesale electricity market while taking operational constraints of network into account and offering services to distribution system operator. This article presents a new framework to incorporate the reliability of distribution network into designing the optimal bidding strategy of a TVPP in day-ahead energy market. In the proposed framework, the TVPP determines the multisteps biddings as pairs of power and price aiming at maximizing its profit in market while minimizing the outage costs due to contingency occurrences. The model is formulated as a bilevel optimization problem in which the upper level maximizes the TVPP's profit regarding network reliability and the lower level clears the market from ISO's viewpoint. Using Karush-Kuhn-Tucker optimality conditions and strong duality theory, the model is converted to a mixed integer linear programming optimization problem. The proposed framework is implemented on the Roy Billinton test system to illustrate the effectiveness of the model.